Degrees of formalization of agricultural entrepreneurs: going beyond registration - THOTO, Fréjus Sourou; JAYNE, Thomas; YEBOAH, Kwame F.; Honfoga, Barthelemy G.; Adégbidi, Anselme (My University, 2021)
The dichotomous view of formalization – ‘registered’ versus ‘not registered’ – is a widely adopted approach for analyzing entrepreneurs and their businesses. It, however, fails to adequately capture the multiple dimensions of the formalization process and limits the scope of interventions to promote business formalization. Hence, this study expands the conceptualization of agribusinesses’ formalization from a dichotomic view to a richer and more dynamic perspective. Using data from a survey of 819 agribusinesses in Benin, we develop a framework that considers multiple dimensions of formalization, namely registration status, compliance with tax law, and compliance with labor law and examine factors that influence the position of entrepreneurs on the formalization continuum. The result shows that agricultural entrepreneurs operate at varying degrees of formalization. Among the surveyed businesses, we found that about 46% were wholly informal, 6% were largely informal, 22% were only registered, 24% were largely formal, and 3% were wholly formal. Entrepreneurs who displayed higher levels of formalization were largely based in urban areas and older, with higher incomes and educational levels. They were also associated with greater awareness of the formalization procedures, had higher tax morality, and perceive a high risk of detection. The result underscores the need to rethink the dichotomous view of formalization and offers insights for targeting policy efforts to increase formalization in agribusinesses.
Keywords: entrepreneurship; formalization; tax; labor; small business; agriculture; Benin